Evaluasi Pengaruh Soda terhadap Kekuatan Kompresi Resin Komposit Flowable Bulk-Fill - Nathania, Cindy; Stefani, Rosita; Eddy; Hadi, Steward (E-Prodenta Journal of Dentistry, 2024)
Background: Flowable bulk-fill composite resin is a direct restoration material and has gained popularity in restorative dentistry for class II restoration. Soda is one of the most consumed drinks by the public and is known to be acidic. Objective: To determine the effect of soda on the compressive strength of flowable bulk-fill composite resin. Methods: This study used 54 cylindrical (diameter: 2 mm; height: 4 mm) flowable bulk-fill composite resin samples of different brands (Beautifil Bulk Flowable, SDR Flow+, Tetric N-Flow Bulk Fill). The samples were divided into 3 control groups and 3 experimental groups. After all groups had been incubated for 24 hours, the control groups were soaked in artificial saliva for 6 days. The experimental groups were soaked in soda for 6 hours, and then for 18 hours in artificial saliva. The solutions were replaced every day, and the pH was measured. The study is performed at a controlled temperature in an incubator at 37°C. After the samples were dried, the compressive strengths of the samples were tested using the Universal Testing Machine. Results: Based on the Two-Way ANOVA test, the compressive strength values between groups of flowable bulk-fill composite resins are not significantly different (p > 0.05). Conclusion : The immersion in soda does not significantly affect the compressive strength of flowable bulk-fill composite resin. Flowable bulk-fill composite resin exhibits relatively high resistance to acidic solutions.